Unveiling mungbean yellow mosaic virus: molecular insights and infectivity validation in mung bean (Vigna radiata) via infectious clones - Balasubramaniam, Madhumitha; Thangavel, Tamilnayagan; Aiyanathan, Karupiah Eraivan Arutkani; Rathnasamy, Sakthi Ambothi; Rajagopalan, Veera Ranjani; Subbarayalu, Mohankumar; Natesan, Senthil; Kanagarajan, Selvaraju; Muthurajan, Raveendran; Manickam, Sudha (Frontiers in Plant Science, 2024)
Yellow mosaic disease (YMD) with typical symptoms of alternating bright yellow to green patches associated with stunting, downward cupping, and wrinkling has been observed in mung bean on agricultural farms in Coimbatore, Tamil Nadu, India. PCR using gene-specific primers indicated the presence of the yellow mosaic virus in symptomatic plants. Rolling circle amplification (RCA) followed by restriction digestion detected 2.7 kb of DNA-A and DNA-B, allowing the identification of a bipartite genome. The full-length genome sequences were deposited in NCBI GenBank with the accession numbers MK317961 (DNA-A) and MK317962 (DNA-B). Sequence analysis of DNA-A showed the highest sequence identity of 98.39% to the DNA-A of mungbean yellow mosaic virus (MYMV)-Vigna radiata (MW736047), while DNA-B exhibited the highest level of identity (98.21%) to the MYMV-Vigna aconitifolia isolate (DQ865203) reported from Tamil Nadu. Recombinant analysis revealed distinct evidence of recombinant breakpoints of DNA-A within the region encoding the open reading frame (ORF) AC2 (transcription activation protein), with the major parent identified as MYMV-PA1 (KC9111717) and the potential minor parent as MYMV-Namakkal (DQ86520.1). Interestingly, a recombination event in the common region (CR) of DNA-B, which encodes the nuclear shuttle protein and the movement protein, was detected. MYMIV-M120 (FM202447) and MYMV-Vigna (AJ132574) were identified as the event’s major and minor parents, respectively. This large variation in DNA-B led us to suspect a recombination in DNA-B. Dimeric MYMV infectious clones were constructed, and the infectivity was confirmed through agroinoculation. In future prospects, unless relying on screening using whiteflies, breeders and plant pathologists can readily use this agroinoculation procedure to identify resistant and susceptible cultivars to YMD.